Hierarchical Anodic TiO2 Nanostructures Formed in Ethylene Glycol/o-H3PO4 Electrolytes for Direct Photocatalysis - Razzaboni, Laura; Altomare, Marco; Pedeferri, Mariapia; Diamanti, Maria Vittoria; Schmuki, Patrik (ChemElectroChem, 2020)
In this work, we describe a simple anodization process of titanium in a hot phosphoric acid/ethylene glycol electrolyte that forms a hierarchically structured photocatalytically active TiO2 layer that consists directly of anatase nanocrystallites. Such anodic layers show, without any annealing, a high photocatalytic degradation activity for AO7 (an azo-dye used as model pollutant) that is higher than the activity of comparable fully crystallized TiO2 nanotube layers. Furthermore, the hierarchically structured layers have a remarkable mechanical bending stability. These features make these novel anodic layers highly promising for applications in flexible substrate based photocatalytic devices.
CRIS-Team Scopus Importer:2020-07-24
Keywords: anodization; hierarchical nanostructure; ortho-phosphoric acid; photocatalysis; TiO